EMPLOYMENT POLICY TRAIL IN BULGARIA - Yordanova, Gabriela (Revista Inclusiones, 2020)
The article presents a policy trail in Bulgaria with focus on a programme funded under the Youth Guarantee initiative in which the aim is to support disadvantaged young people into employment (employment focus). In order to gather information on the participation of people in training and employment, qualitative methods are used - content analysis of documents and in-depth interviews. The article analyses the characteristics of specific program; access and barriers; possible benefits; learning lessons. Conclusions are made and possible actions are proposed (in a national / regional context).